On the optimal strategy for the hedge fund manager:An experimental investigation - Yudistira Permana (Cogent Business & Management, 2020)
This paper examines the empirical validity of Nicolosi's optimal strategy for a hedge fund manager under a specific payment contract. The contract specifies that the manager's payment consists of a fixed payment and a variable payment, which is a performance-based payment. The model assumes that the manager is an Expected Utility agent who maximises his/her expected utility by buying and selling the asset at appropriate moments. Nicolosi derives the optimal strategy for the manager by assuming a Black-Scholes setting where the manager can invest either in an asset or in a money account. The asset price follows geometric Brownian motion and the money account has a constant interest rate. I experimentally test Nicolosi's optimal strategy to investigate whether the agents invest according to the optimal strategy. To meet the aim of this paper, I compare the empirical support of the optimal strategy with other possible strategies. The results show that Nicolosi's optimal strategy receives strong empirical support for explaining the subjects' behaviour, though not all of the subjects follow the optimal strategy. Having said this, it seems that the subjects somehow follow the intuitive prediction of Nicolosi's optimal strategy in which the decision-maker responds to the difference between the managed portfolio and the benchmark to determine the portfolio allocation.
Keywords: G11; C91; 650; fund manager; portfolio strategy; laboratory experiment